The Effect of Type and Spray Frequency of Leri on Growth of Phalaenopsis sp. Orchid after Acclimatization - PURNAMI, NI LUH GEDE WIDYA; YUSWANTI, HESTIN; ASTININGSIH, A.A. MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.1, Januari2014, 2014)
ABSTRACT The Effect of Type and Spray Frequency of Leri on Growth of Phalaenopsis sp. Orchid after Acclimatization This research purpose was to know about interaction between type and spray frequency of leri and also single impact of this treatment to Phalaenopsis sp. orchid growth after acclimatization. The location of research was in Kerobokan, Badung district in May–September 2011. Used randomized block design, orchid seedlings were treated by combination type of leri such as leri from Ciherang white rice, Ciherang brown rice, brown rice of red local type and spray frequency such as once in 2 days, once in 4 days, once in 6 days also once in 8 days  with 3 repetition. The result showed that brown rice of red local type and once in 4 days spray frequency each had the highest variable result on height accretion of plant (4,08 and 3,89 mm), length of roots (47,15 and 45,40 mm), fresh weight of upper plant organ (895 and 896,67 mg) and also dry weight total of plant (55 and 55,56 mg). Interaction between brown rice of red local type and spray frequency once in 4 days was the best combination to increase orchid seedling growth after acclimatization. Keywords : orchid, leri, acclimatization.
Keywords: orchid, leri, acclimatization.